2001
DOI: 10.1067/mtc.2001.111417
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning with opening of mitochondrial adenosine triphosphate–sensitive potassium channels or Na+/H+ exchange inhibition: Which is the best protective strategy for heart transplants?

Abstract: These data suggest that cardioprotection conferred by the Na(+)/H(+) exchange inhibitor cariporide is additive to that of ischemic preconditioning and might effectively contribute to improve donor heart preservation during cardiac transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…From a surgical standpoint, the approach of NHE inhibition is particularly appealing because in the GUARDIAN trial the most pronounced cardioprotective effect of cariporide was observed in the subset of patients who underwent coronary artery bypass graft surgery [6]. This is consistent with the observation that a prerequisite for NHE inhibitors to be fully cardioprotective is their sustained presence in myocardial tissue from the onset of ischemia, a timing of administration which easily fits the practical conduct of cardiac operations [5,8].…”
Section: Introductionsupporting
confidence: 58%
“…From a surgical standpoint, the approach of NHE inhibition is particularly appealing because in the GUARDIAN trial the most pronounced cardioprotective effect of cariporide was observed in the subset of patients who underwent coronary artery bypass graft surgery [6]. This is consistent with the observation that a prerequisite for NHE inhibitors to be fully cardioprotective is their sustained presence in myocardial tissue from the onset of ischemia, a timing of administration which easily fits the practical conduct of cardiac operations [5,8].…”
Section: Introductionsupporting
confidence: 58%
“…Pretreatment of rat hearts with an adenosine analog prior to harvesting and storage in the Euro-Collins solution for 8 hours improved functional recovery at reperfusion [237]. In another study, IPC combined with Na + /H + antiporter inhibition improved cardiac function in rat hearts after 4 hours of storage at 4°C in Celsior solution and extracorporeal reperfusion [238]. K ATP channel activation mimicked the protective effect of IPC in hearts after prolonged hypothermic storage [239241].…”
Section: Pc and Postc In Experimental Heart Transplantationmentioning
confidence: 99%
“…Animal models have confirmed that cariporide is beneficial in the setting of donor preservation especially when given during ischaemia and reperfusion. 29,54 Optimising Ca 2+ handling in the ischaemic heart is a critical role of preservative solutions. By limiting the Ca 2+ content within the preservative solution, the gradient favouring Ca 2+ entry during ischaemia is reduced.…”
Section: Improved Ion Homeostasismentioning
confidence: 99%